2014
DOI: 10.1039/c4cp02580f
|View full text |Cite
|
Sign up to set email alerts
|

Field-enhanced bulk conductivity and resistive-switching in Ca-doped BiFeO3 ceramics

Abstract: Versión / Versió:Pre-print Cita bibliográfica / Cita bibliogràfica (ISO 690):MASÓ, Nahum, et al. Field-enhanced bulk conductivity and resistive-switching in Ca-doped BiFeO 3 ceramics. Physical Chemistry Chemical Physics, 2014, vol. 16, no 36, p. 19408-19416.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 33 publications
(89 reference statements)
2
23
0
4
Order By: Relevance
“…It was shown recently that electronic conduction can be introduced into Y‐doped ZrO 2 under the action of a small dc bias at high temperature . Similar conductivity increases had been observed in other acceptor‐doped systems such as Mg‐ or Zn‐doped BaTiO 3 perovskite but in those cases, the conductivity was also sensitive to p O 2 in the surrounding atmosphere, from which it was possible to determine that the carriers were p‐ type. As far as we are aware, there are no reports on the possible sensitivity of the conductivity of 8YSZ to higher values of p O 2.…”
Section: Introductionsupporting
confidence: 62%
“…It was shown recently that electronic conduction can be introduced into Y‐doped ZrO 2 under the action of a small dc bias at high temperature . Similar conductivity increases had been observed in other acceptor‐doped systems such as Mg‐ or Zn‐doped BaTiO 3 perovskite but in those cases, the conductivity was also sensitive to p O 2 in the surrounding atmosphere, from which it was possible to determine that the carriers were p‐ type. As far as we are aware, there are no reports on the possible sensitivity of the conductivity of 8YSZ to higher values of p O 2.…”
Section: Introductionsupporting
confidence: 62%
“…Recently, Masó and West [9] demonstrated that electronic conduction is introduced into YSZ08 under the action of a small dc bias at high temperature in air. Similar conductivity changes were seen with acceptor-doped titanate perovskites including Ca-, Zn-and Mgdoped BaTiO 3 [10][11][12] and Ca-doped BiFeO 3 [13], which all show enhanced conductivity on either increasing pO 2 in the measuring atmosphere or application of a small dc bias. The enhanced conductivity was attributed to ionization of underbonded O 2ions in the vicinity of acceptor dopants leading to hole creation on oxygen which conceptually, is the same as the creation of Oions:…”
Section: Introductionsupporting
confidence: 56%
“…The estimated work function is 4.2 eV and its Fermi level is about 0.2 eV, which lies below the bottom of conduction band [7]. BiFeO 3 is a p-type semiconductor [33][34][35][36], whose band gap varies from 2.0 to 2.7 eV and its Fermi level lies close to its valance band. Here the band gap of BFO is calculated to be 2.07 eV according to the UV-vis DRS spectra.…”
Section: Discussion On Mechanismmentioning
confidence: 99%